2020
DOI: 10.26434/chemrxiv.11833503.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis of Proteins by Automated Flow Chemistry

Abstract: <p>Ribosomes produce most proteins of living cells in seconds. Here we report highly efficient chemistry matched with an automated fast-flow instrument for the direct manufacturing of peptide chains up to 164 amino acids over 328 consecutive reactions. The machine is rapid - the peptide chain elongation is complete in hours. We demonstrate the utility of this approach by the chemical synthesis of nine different protein chains that represent enzymes, structural units, and regulatory factors. After purific… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Since Route-2 applies much shorter reaction times compared to Route-1, it demonstrated that time is a limiting factor in reaching high conversion in each reaction step. Based on Fick's second law, 7,8,16,17 the temperature was elevated to 90 ºC while maintaining short reaction periods, fast stirring, and low reagent concentrations. Peptide-a was synthesized via Route-3 (30 sec reactions, 90 °C), which is almost identical to Route-2, only that the entire process was performed at 90 °C instead of 30 °C (Fig.…”
Section: Initial Evaluation Of Htfspsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Route-2 applies much shorter reaction times compared to Route-1, it demonstrated that time is a limiting factor in reaching high conversion in each reaction step. Based on Fick's second law, 7,8,16,17 the temperature was elevated to 90 ºC while maintaining short reaction periods, fast stirring, and low reagent concentrations. Peptide-a was synthesized via Route-3 (30 sec reactions, 90 °C), which is almost identical to Route-2, only that the entire process was performed at 90 °C instead of 30 °C (Fig.…”
Section: Initial Evaluation Of Htfspsmentioning
confidence: 99%
“…2,4,5 Increased reaction durations, high reagent concentrations, and elevation of reaction temperature are commonly applied to accelerate reactions on a solid support. 12,17 However, the effect of mixing efficiency on SPPS processes is not commonly discussed. 4,5,16 To perform an efficient SPPS process, one needs to consider all conditions that can affect the parameters related to Fick's second law of diffusion (Equation 1), including mixing, which is setup-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…The above results confirm that peptides containing His and Cys can be synthesized by HTFSPS without using special building blocks or deviating from the standard cycle protocol maintaining the high temperature. 17…”
Section: Htfsps Does Not Cause Significant Epimerizationmentioning
confidence: 99%
“…2,4,5 Increased reaction durations, high reagent concentrations, and elevation of reaction temperature are commonly applied to accelerate reactions on a solid support. 12,17 However, the effect of mixing efficiency on SPPS processes is not commonly discussed. 4,5,16 To perform an efficient SPPS process, one needs to consider all conditions that can affect the parameters related to Fick's second law of diffusion (Equation 1), including mixing, which is setup-dependent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation